PENINGKATAM PEMBELAJARAN KARYA TULIS ILMIAH (KTI) DENGAN METODE INQUIRY BASED LEARNING PADA SISWA KELAS XI IPA SMA NEGERI 2 - Kamilah Kamilah (STKIP ROKANIA, 2021)
This research is a classroom action research, which aims to determine the improvement of scientific work learning with the Inquiry Based Learning method. The object of the research is students of class XI IPA SMA Negeri 2 Rambah Pasir Pengaraian with a total of 30 students. This classroom action research consists of 2 cycles, the first cycle with four actions or learning meetings and the second cycle with three actions. The results of data analysis were carried out by observation, giving questionnaires and learning outcomes tests. Based on the results of the study, it can be concluded that with the Inquiry Based Learning method in learning Indonesian, Class XI students of SMA Negeri 2 Rambah, Rokan Hulu Regency are more active, their interests and skills are much better which ultimately affects the increase in learning outcomes. This can be seen from the table Comparison of the average value of the test results before using the Inquiry Based Learning learning method. The average value of the pre-test before using the Inquiry Based Learning method was 69.6. The average score for the first meeting was 76.00. At the second meeting it increased to 77.93, at the third meeting in the second cycle the average value also increased again to 80.17. The average value for the fourth meeting increased again from the previous meeting, which was 92.97. From these data, it is clear that there is a significant increase before using the Inquiry Based Learning method and after using the Inquiry Based Learning method.